2(x+5)=6x+2

Simple and best practice solution for 2(x+5)=6x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+5)=6x+2 equation:


Simplifying
2(x + 5) = 6x + 2

Reorder the terms:
2(5 + x) = 6x + 2
(5 * 2 + x * 2) = 6x + 2
(10 + 2x) = 6x + 2

Reorder the terms:
10 + 2x = 2 + 6x

Solving
10 + 2x = 2 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
10 + 2x + -6x = 2 + 6x + -6x

Combine like terms: 2x + -6x = -4x
10 + -4x = 2 + 6x + -6x

Combine like terms: 6x + -6x = 0
10 + -4x = 2 + 0
10 + -4x = 2

Add '-10' to each side of the equation.
10 + -10 + -4x = 2 + -10

Combine like terms: 10 + -10 = 0
0 + -4x = 2 + -10
-4x = 2 + -10

Combine like terms: 2 + -10 = -8
-4x = -8

Divide each side by '-4'.
x = 2

Simplifying
x = 2

See similar equations:

| 6(5v+4)=84 | | (x)=0 | | Csquared-5=75 | | 4x+5=3x+23 | | (4a-8b)=(7a+6b) | | cosx*cosx*cosx= | | 7x-3=3x+17 | | 2x-y+50=180 | | 2x-x+50=180 | | x-20-x^2= | | 3-2x=-6-8x | | 9+x^2-6x= | | 4[x-(3-2x)]=3(x+11) | | 32x-5(3x)+4=0 | | 4x-15=24 | | 3x^2-x-72=0 | | (3/4)-(1/2)n=(5/8) | | 5(6-4)=u+21 | | 3(x+8)=75 | | 25=5t | | 8=2w | | 2=2(3x+5)-2 | | 2(3x+4)+3=5x+20 | | Y=4cos(2-3x) | | 6p-3=39 | | 2y+5=y | | 14m+5n-6m+8n= | | -1+6p=23 | | 6p-1=23 | | -5x-10=17 | | 100+4x=400 | | 6-3p=42 |

Equations solver categories